WEWENANG PENYELENGGARA JALAN OLEH PEMERINTAH KABUPATEN BERDASARKAN UNDANG-UNDANG REPUBLIK INDONESIA NOMOR 38 TAHUN 2004 TENTANG JALAN (STUDI DI WILAYAH KABUPATEN SINTANG) - Victor Emanuel (Universitas Kapuas Sintang, 2021)
Road is a vital transportation infrastructure for the economic and social growth of its people. An accessible of road transport as a physical infrastructure facility for the better purpose of the its community. In case, the road damage in Sintang Regency area needs to be handled. Therefor, road organizer’s authority is required based on the provisions in Legal System the Republic of Indonesia about road Number 38 the years of 2004. This method of this study is a sociological juridical with a descriptive analytical research characteristics.As a result, the goverment’s authority of Sintang district or as the road organizer are based on a legal sytem article 16 about road number 38 the years of 2004 called as the authority of attribution. This implementation of this authority is technically by the Public Works Department of Sintang District. The causes of road damage for both of National and Provincial are because The government of Sintang District have no authority for handled. The government of Sintang DistrictGovernment only providing road damage reports .In conclusion, the authority of the government of Sintang District as the road organizer are based on a legal sytem article 16 about road number 38 the years of 2004. This authority as the authority of attribution. In technically, it is carried out by the Public Works Department of Sintang District. The roads in Sintang Regency consist of National roads, Provincial roads and Regency roads. In hence, it can be inferred that barrier factors for Government’s authority of Sintang District as road organizer, namely; the legal structure factors, the substance factors and the culture factors.